Antiproton stopping power data for radiation therapy simulations - Bailey, Jackson; Kadyrov, Alisher; Abdurakhmanov, Ilkhom; Fursa, Dimity; Bray, Igor (Elsevier, 2016)
Stopping powers of H, He, H2, and H2O targets for antiprotons have been calculated using a convergent close-coupling method. For He and H2 targets electron-electron correlations are fully accounted for using a multiconfiguration approximation. Two-electron processes are included using an independent-event model. The water molecule is described using a neon-like structure model with a pseudo-spherical potential. Results are tabulated for the purpose of Monte Carlo simulations to model antiproton transport through matter for radiation therapy.